Quantitative Calculation of Horizontal Well Reservoir Boundary Using Shear Wave Reflection Technique - CHEN Huayong; LIN Jingqi; GONG Jie; ZHOU Jufeng; LINGHU Song; ZHENG Yujun; GUO Xuyang (Cejing jishu)
Horizontal wells and volumetric fracturing techniques are used to develop low permeability conglomerate reservoirs. Boundaries of reservoir is key parameters for the evaluation of well configuration and hydraulic fracturing design. Geological modeling, resistivity inversion, and gamma inversion are affected by the modeling methods and by the depth of investigation, and the accuracy of boundary calculation is low, making it hard to quantify the boundaries. In the low permeability reservoirs in the Junggar basin, the formation inclination angles are small; the wave impedances contrast of reservoir and cap rock are large; horizontal well trajectory angles are nearly 90°. In this environment, the propagation of dipole shear wave is perpendicular to reservoir boundaries, with strong reflection signals at boundaries. Based on these characteristics, a method of quantitative calculation of reservoir boundary in horizontal wells by using shear wave reflection technique is proposed. This method can accurately calculate the distance between horizontal wellbores and the boundaries only based on orthogonal dipole acoustic wave data. Then, based on formation occurrence, thickness, and well configuration, altitudes of reservoir boundaries can be obtained. As a result, vertical profiles of horizontal well reservoir, well configuration, and upper and lower interlayers can be determined. The study improves the evaluation accuracy of horizontal well reservoir and well configurations, and it provides quantitative references for the commercial development of low permeability conglomerate reservoirs.